Mechanical Properties and Hardening Mechanism of Magnesium Ammonium Phosphate Cements Modified by Fly Ash - Ran Hai; Jingyu Zhang; Junxia Liu; Cun Hui; Fei Yang (Advances in Civil Engineering)
High hydration heat and poor water resistance are the main factors restricting the application of magnesium ammonium phosphate cement (MAPC). To alleviate the problem, fly ash was used to partially replace dead-burned MgO and NH4H2PO4 in this paper. The effect of fly ash content on MAPC properties, such as setting time, fluidity, mechanical properties, and water resistance, was investigated. The micromorphology of hydration products and the influence mechanism of fly ash on the macrocharacteristics and hydration process of MAPC were also discussed. The results showed the mechanical properties of fly ash-modified MAPC decreased with the increase of the fly ash content, but their increments at later hydration were greater than the control MAPC. Meanwhile, fly ash could improve the water-resistance significantly and reduce the total hydration heat. The fly ash refined the struvite crystal and increased the compactness of MAPC, although no obvious hydration products of fly ash were observed. So, when the content of fly ash is 30 wt%, the MAPC has appropriate mechanical properties, while its water resistance is significantly improved, and its hydration heat is reduced compared with the control group.